1987
DOI: 10.1210/endo-120-2-685
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Functional Communication between Folliculo-Stellate Cells and Hormone-Secreting Cells in Perifused Anterior Pituitary Cell Aggregates*

Abstract: Dispersed anterior pituitary cells from adult female rats were separated by gradient sedimentation at unit gravity. The small-sized cell population on top of the gradient consisted of 65.6 +/- (SE) 4.2% (n = 8) cells immunoreactive to antiserum against S-100 protein, a marker of folliculo-stellate (FS) cells in rat pituitary. The corresponding fraction derived from adult male or immature female rats were also enriched in S-100 positive cells but to a lower extent. Only small numbers of S-100 positive cells wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
94
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 171 publications
(101 citation statements)
references
References 0 publications
7
94
0
Order By: Relevance
“…In vitro studies using static monolayer cultures, with pituitary cells (46) or enriched FS cells (23) plated at high density, resulted in the formation of confluent monolayers and also 'tight' diffusion barriers and dome formation (23). In our studies, however, we used three-dimensional (3D) re-aggregated cell cultures, obtained by gyratory shaking of isolated pituitary cells in suspension, yielding a more histotypic cell culture system of the rat anterior pituitary (24,25). Permeability studies of the interstitial environment in FS cell-enriched cell aggregates (47) confirmed the leakiness of intercellular junctions in vitro, similar to intercellular junctions in the rat anterior pituitary in situ (3,26,45).…”
Section: Morphology Of Fs Cells and Compartmentalization Of The Antermentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies using static monolayer cultures, with pituitary cells (46) or enriched FS cells (23) plated at high density, resulted in the formation of confluent monolayers and also 'tight' diffusion barriers and dome formation (23). In our studies, however, we used three-dimensional (3D) re-aggregated cell cultures, obtained by gyratory shaking of isolated pituitary cells in suspension, yielding a more histotypic cell culture system of the rat anterior pituitary (24,25). Permeability studies of the interstitial environment in FS cell-enriched cell aggregates (47) confirmed the leakiness of intercellular junctions in vitro, similar to intercellular junctions in the rat anterior pituitary in situ (3,26,45).…”
Section: Morphology Of Fs Cells and Compartmentalization Of The Antermentioning
confidence: 99%
“…The electrophysiological properties of presumed FS cells have been studied in detail in the amphibian Xenopus laevis (22). Older studies have especially focussed on the transport epithelial characteristics of FS cells (23) and the contribution of FS cells to the regulation of the pituitary interstitial environment (23), and to paracrine communication with pituitary hormone-secreting cells (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…Folliculo-stellate cells do not secrete hormones and have characteristics in common with monocytic phagocytes. Initially believed to be inert cells there is evidence that folliculo-stellate cells secrete substances including IL-6 which are involved in the paracrine control of hormone secretion (Baes et al, 1987). There is no direct evidence at present that IL-6 is synthesized or released by any of the normal hormone secreting cells.…”
Section: Hypothalamusmentioning
confidence: 99%
“…Therefore, it is not reasonable to rule out the possibility that increased physical connection between TtT/ GF cells and gonadotropes in PACAP-treated co-cultures underlay the paracrine action of PACAP-treated TtT/GF cells. However, this possibility appears minimal because of the results from experiments using CM and by analogy that physical connection between FS cells and growth hormone/prolactin-secreting cells does not mediate the functional communications between these cell types [1]. On the other hand, the effect of PACAP on normal gonadotrope cell growth is not clear, although PACAP stimulates proliferation of αT3-1 cells [32], a transformed cell line that express α-subunit, but not β-subunit, genes of gonadotropins [39].…”
Section: Discussionmentioning
confidence: 99%